Droit, littérature et traduction : rencontre sur le terrain de la fiction. - Dang, Thanh-Tram. (University of Ottawa (Canada), 2002)
This thesis examines the unique perspective that the Law and Literature movement can bring to the study of legal translation in literature and how the movement can further the reflection on the task of the legal translator. Charles Dickens' legal novel Bleak House (La Maison d'Apre-Vent) will serve to foreground the main problems of legal translation, both theoretical and practical, and special emphasis will be put on the many traps of legal language. The object of this thesis is to foster a better understanding of law and its social repercussions, and of how language contributes to the elaboration and interpretation of law.
Keywords: Law.